Nanopore 16S amplicon sequencing enables rapid detection of pathogen in knee periprosthetic joint infection - Hyuk-Soo Han; Du Hyun Ro; Jeehyeok Chung; Narae Kim; Jangsup Moon (Elsevier, 2022)
Objectives: We investigated whether nanopore 16S amplicon sequencing is capable of bacterial identification in patients with knee prosthetic joint infection (PJI), and we compared its efficacy with conventional culture studies. Methods: In total, 36 patients who had clinical manifestation suspected of PJI were enrolled in this study. To begin, synovial fluids were aspirated from the affected knee using aseptic technique and tissues specimens were obtained during the surgery. Next, DNA was extracted from the synovial fluid or tissues, and 16S rDNA PCR was performed. In PCR positive cases, nanopore amplicon sequencing was then performed for up to 3 h. The results of amplicon sequencing were compared to those of conventional culture studies. Results: Of the 36 patients enrolled, 22 were classified as true infections according to the MSIS criteria whereas 14 were considered uninfected. Among the 22 PJI cases, 19 cases were culture positive (CP-PJI) while three cases were culture negative (CN-PJI). In 14 of 19 (73.7 %) CP- PJI cases, 16S sequencing identified concordant bacteria with conventional culture studies with a significantly shorter turnaround time. In some cases, nanopore 16S sequencing was superior to culture studies in the species-level identification of pathogen and detection of polymicrobial infections. Altogether, in the majority of PJI candidate patients (32 of 36, 88.9 %), 16S sequencing achieved identical results to cultures studies with a significantly reduced turnaround time (100.9 ± 32.5 h vs. 10.8 ± 7.7 h, p < 0.001). Conclusions: Nanopore 16S sequencing was found to be particularly useful for pathogen identification in knee PJI. Although the sensitivity was not superior to culture studies, the nanopore 16S sequencing was much faster, and species-level identification and detection of polymicrobial infections were superior to culture studies.